Grand Hotel Abyss the lives of the Frankfurt School - Jeffries, Stuart 1962- (Verso, 2016)
"Grand Hotel Abyss investigates the lives and afterlives of the critical theorists who formed the Frankfurt School"...
Keywords: Geschichte 1900-2000; Ideengeschichte; Geschichte; Frankfurt school of sociology -- History; Critical theory -- History -- 20th century; Frankfurt school of sociology -- Biography; Sociologists -- Germany -- Biography; Philosophers -- Germany -- Biography; Sociology -- Germany -- History -- 20th century; Kritische Theorie; Deutschland; Germany -- Intellectual life -- 20th century; Biografie